The Effect of Mental Exercise and Muscle Endurance on the Shots of Archery Athletes - Pijar Kuncoro Yudho; Mugiyo Hartono; Sri Sumartiningsih (JUARA : Jurnal Olahraga, 2022)
This study aimed to determine and analyze the effect of imagery training and circuit training using tools, to analyze the effect of imagery training and circuit training without tools, to analyze the effect of self-hypnosis training and circuit training using tools, to analyze the effect of self-hypnosis and circuit training without equipment. Tools and the interaction between mental training and resistance to archery ability. This study used an experimental method with a 2x2 factorial design. This population consisted of 32 archers from South Sumatra. The sample used was total sampling. The data analysis technique used analysis of variance (ANOVA) at a significance level of (0.05). The results showed 1) There was a difference in the effect between imagery training and circuit training using a tool on the results of shots from a distance of 50, 40 and 30 meters. 2) there are differences in the effect of imagery training and circuit training without tools on the results of 50, 40 and 30 meters distance shots. 3) There is a difference in the effect of self-hypnosis training and circuit training using a tool on the results of shots from a distance of 50, 40 and 30 meters. 4) There is a difference in the effect of self-hypnosis training and circuit training without tools on the results of shots from 50, 40 and 30 meters distance. 5) There is no interaction between mental training and muscle endurance in the results of 50,40, and 30 meters of archery shots. The conclusion of this study shows that circuit training using tools and mental imagery, self-hypnosis is more significant. The results can be seen in the average increase in the total score, namely 31.13 and 31.12. And the increase in circuit training without tools and imagery, self-hypnosis, the average increase in the total score is 10.00 and 13.5, and there is no interaction between mental exercise and muscle endurance on the results of shots from a distance of 50, 40 and 30 meters.